2016
DOI: 10.1021/acs.macromol.5b02282
|View full text |Cite
|
Sign up to set email alerts
|

Highly Flexible and Visibly Transparent Poly(vinyl alcohol)/Calcium Zincate Nanocomposite Films for UVA Shielding Applications As Assessed by Novel Ultraviolet Photon Induced Fluorescence Quenching

Abstract: Herein we report the successful fabrication of highly flexible, reversibly stretchable, transparent, and conductive poly­(vinyl alcohol) (PVA) nanocomposite (NC) films with a hydrophobic surface by reinforcing varying amounts, viz., 0, 0.5, 1, 2, and 4 wt %, of calcium zincate (Ca0.2Zn0.8O) nanofillers. The developed nanocomposite films show appreciable UVA screening efficacies as established by a novel (UV-transillumination studies) method. The Fourier transform infrared (FTIR) studies reveal a positive inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…At lower frequency region, the dielectric constant of the composites depends only on space charge polarization hence the dielectric constant is maximum because the space charges are able to follow the applied electric field particularly at lower frequency region. Whereas at high frequencies they get fewer time limits to build up space charges and thus, are unable to undergo relaxation hence the dielectric constant remains in a steady state at higher frequency region and this plateau region is actually attributed to 3 remaining polarization mechanisms …”
Section: Dielectric and Electrical Propertiesmentioning
confidence: 99%
“…At lower frequency region, the dielectric constant of the composites depends only on space charge polarization hence the dielectric constant is maximum because the space charges are able to follow the applied electric field particularly at lower frequency region. Whereas at high frequencies they get fewer time limits to build up space charges and thus, are unable to undergo relaxation hence the dielectric constant remains in a steady state at higher frequency region and this plateau region is actually attributed to 3 remaining polarization mechanisms …”
Section: Dielectric and Electrical Propertiesmentioning
confidence: 99%
“…It is observed that the dielectric constants of the P(VDF‐HFP)/BFO‐SO 3 H and P(VDF‐HFP)/BFO‐SO 3 H/SiC composites with SiC loading decrease with frequency over the whole frequency range but i) in case of P(VDF‐HFP)/BFO‐SO 3 H/SiC composites, the dielectric constant shows a rapid decrease with frequency at the low‐frequency range and ii) in case of P(VDF‐HFP)/BFO‐SO 3 H composite the plot show frequency dependence behavior similar to that of P(VDF‐HFP)/BFO‐SO 3 H/SiC composites but remains almost same at higher frequency region. This can be attributed to interfacial polarization which is mainly active at lower frequency region . If we compare the dielectric constant of three phases, two phases and pure polymer the dielectric constant of three phase's composites is found to be much ahead of other two .…”
Section: Dielectric and Electrical Propertiesmentioning
confidence: 94%
“…In recent years, some nano‐inorganic particles (ZnO, TiO 2 CeO 2 and Calcium zincate with wide band gap) and organic UV absorbers (e. g., avobenzone, oxybenzone, and octyl methoxycinnamate) have been used as UV shielding materials with good transparency in visible region. Some novel designs of nanomaterials also were applied in developing the UV shielding composite films, such as hybrid organic‐inorganic films .…”
Section: Introductionmentioning
confidence: 99%
“…Some novel designs of nanomaterials also were applied in developing the UV shielding composite films, such as hybrid organic‐inorganic films . In addition, polymers, such as poly (vinyl chloride) (PVC), Poly(vinyl alcohol) (PVA), Poly(ethylene terephthalate) (PET), Poly(ethylene glycol‐co‐1,4‐cyclohexanedimethanol terephthalate) (PETG), poly(lactic acid), has been used widely as UV shielding substrates. Whereas the above‐mentioned polymers are generally refined from the nonrenewable petroleum resource.…”
Section: Introductionmentioning
confidence: 99%